SERVICE DESK – Uma análise do grau de maturidade nos processos e serviços prestados pela central de serviços da TI ASAV: um estudo de caso na instituição de ensino superior UNISINOS - Oliveira, Rodrigo Amaral de (Universidade do Vale do Rio dos Sinos, 2014)
The constant search for excellence in Management Services in the field of Information Technology (IT) is now the goal of any organization. The IT Service Management involves the support and delivery of technology services in accordance with the requirements of the organization and its business focusing on service quality and customer oriented their focus. The use of best practices and methodologies that assist the management of IT services has become an essential practice for successful delivery of services. The Service Desk is one of the disciplines of the ITIL framework (Information Technology Infrastructure Library) which has the strategic role of communication and support of the delivery of IT services defined as central point of contact between customer and service. The objective of this study is to evaluate the level of maturity of processes and services provided by the IT Service Desk ASAV the institution of higher education UNISINOS based on internationally recognized best management practices for IT services. This study used a single case study method, allowing to identify how the processes are created and how is the service delivery. Data analysis for the study were raised and finally propose improvements to management of IT services.
Keywords: Processos e serviços; COBIT; Nível de maturidade; Service desk; Process and services; ITIL; Maturity level